A jury of her peers American women writers from Anne Bradstreet to Annie Proulx - Showalter, Elaine 1941- (A Borzoi book, 2009)
In a narrative of immense scope and fascination--spanning nearly 400 years and brimming with Showalter's characteristic wit and incisive opinions--readers are introduced to more than 250 female writers, both famous and little known